Studying High-Mass Microquasars with HAWC - Hwang, Se Yeon; Son, Youngwan; Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; et al. (Proceedings of Science, 2022)
High-mass microquasars (HMMQs) are powerful particle accelerators, but their mechanism of the high-energy emission is poorly understood. To date, only a handful of these particle engines have ever been observed to emit gamma-ray photons and are thus potential TeV gamma-ray emitters. In this work, we study four HMMQs, namely, LS 5039, Cyg X-1, Cyg X-3, and SS 433 using the data from the High Altitude Water Cherenkov (HAWC) observatory. We perform time dependent analyses on each HMMQ to look for any periodic variations in their flux. We produce light curves using the HAWC daily maps from which we generate Lomb-Scargle periodograms. By analysing the significance of the periodogram peaks, we assess whether or not HAWC is sensitive to orbitally modulating TeV gamma-ray flux in the four HMMQs.
CRIS-Team Scopus Importer:2024-12-16